2018
DOI: 10.1002/jcb.27032
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling promotes angiogenesis and improves cardiac function after myocardial infarction

Abstract: Currently, the role of Notch signaling during myocardial infarction (MI) remains controversy. In this study we used in vitro and in vivo approaches to investigate the role of Notch signaling in MI. Using cultured human umbilical vein endothelial cells exposed to hypoxia/reoxygenation (H/R), we demonstrated that H/R inhibited the proliferation, VEGF secretion, and tube formation of HUVECs, and these effects were correlated with the inhibition of Notch signaling. Furthermore, these effects were antagonized by ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Furthermore, previous studies have demonstrated that miR‐210 plays crucial roles by targeting a large number of genes (X.‐L. Zhou et al, ), including NOTCH1 (Y. L. Lou et al, ). Indeed, in the human placenta, NOTCH1 participates in the development of the EVT lineage (Sandra et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies have demonstrated that miR‐210 plays crucial roles by targeting a large number of genes (X.‐L. Zhou et al, ), including NOTCH1 (Y. L. Lou et al, ). Indeed, in the human placenta, NOTCH1 participates in the development of the EVT lineage (Sandra et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that miR-210 plays critical roles in various pathophysiological processes, such as angiogenesis, ischemia, inflammation, and tumorigenesis (Chan & Loscalzo, 2010;Herr et al, 2011). Furthermore, previous studies have demonstrated that miR-210 plays crucial roles by targeting a large number of genes (X.-L. Zhou et al, 2018), including NOTCH1 (Y. L. Lou et al, 2012). Indeed, in the human placenta, NOTCH1 participates in the development of the EVT lineage (Sandra et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Neovasculogenesis has the potential to salvage ischemic myocardium at early stages post-MI. Notch1 signaling plays a critical role in postnatal angiogenesis including cardiac angiogenesis during ischemia (Yoshida et al, 2014;Zhou et al, 2018), thus enhancing survival of cardiac cells. Notch1 activation promotes VSMC differentiation of CDC through an RBPJdependent signaling pathway (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In embryos, the Notch signaling pathways function mainly in heart morphogenesis and coronary angiogenesis (Quillard and Charreau, 2013; Luxan et al, 2016a, b). In adults, this pathway may contribute to endothelial barrier maintenance and regulate angiogenesis (Zhou et al, 2018). However, since all its components are present, it can be activated after the appearance of specific stressors, which in the heart can be ischemia (Li et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that during cardiac ischemic processes, such as acute myocardial infarction, there is a notch‐driven trend toward increasing cardiac progenitor cell differentiation. Most likely, this process will replace lost cardiomyocytes, decrease conversion from fibroblasts to myofibroblasts, and promote collateral vessels by angiogenesis, as a part of the overall effort to further reduce the scar area (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%